Iodine-125 seed brachytherapy combined with pembrolizumab for advanced non-small-cell lung cancer after failure of first-line chemotherapy: A report of two cases and literature review - Yuan, Mingli; Wang, Liangchao; Xiao, Yang; Guo, Xiaoqun; Hu, Yi (Journal of Contemporary Brachytherapy, 2023)
Although immunotherapy regimens for advanced non-small-cell lung cancer (NSCLC) improve survival in selected sub-populations, their efficacy remains far from ideal due to underlying resistance; therefore, multimodal combination strategies are needed to optimize their efficacy. In our report, two patients with advanced NSCLC with negative targetable mutations, who had failed first-line chemotherapy were treated with combined therapy of computed tomography (CT)-guided percutaneous iodine-125 seed implantation and pembrolizumab. After combination treatment, both patients achieved partial response (PR), and sustained a long progression-free survival (PFS) without obvious therapy-related adverse reactions. Iodine-125 seeds bring no long-term adverse events and effectively amplify anti-tumor immune response induced by immunotherapy; thus, this combined therapy might be a promising alternative for NSCLC.